Safe Nanocomposite‐Mediated Efficient Delivery of MicroRNA Plasmids for Autosomal Dominant Polycystic Kidney Disease (ADPKD) Therapy. Issue 5 (23rd January 2019) - Tsai, Yen‐Chang; Teng, I‐Ling; Jiang, Si‐Tse; Lee, Yi‐Che; Chiou, Yuan‐Yow; Cheng, Fong‐Yu
Abstract: There is currently no cure for gene mutation‐caused autosomal dominant polycystic kidney disease (ADPKD). Over half of patients with ADPKD eventually develop kidney failure, requiring dialysis or kidney transplantation. Current treatment modalities for ADPKD focus on reducing morbidity and mortality from renal and extrarenal complications of the disease. MicroRNA has been shown to be useful in treating ADPKD. This study combines anti‐miRNA plasmids and iron oxide/alginate nanoparticles for conjugation with antikidney antibodies. These nanocomposites can specifically target renal tubular cells, providing a potential treatment for ADPKD. Magnetic resonance imaging and in vivo imaging system results show effective targeting of renal cells. Anti‐miRNA plasmids released from the nanocomposites inhibit cell proliferation and cyst formation in the PKD cellular and animal models. The results suggest the novel combination of the anti‐miRNA plasmids and nanomaterials provides potential clinical implications for ADPKD treatment. Abstract : A novel kidney‐specific targeting nanocomposite composed of safe and United States Food and Drug Administration‐approved Fe3 O4 nanoparticles and alginate is synthesized. The nanocomposites show efficiently targeting and therapeutic efficiency using cellular and animal polycystic kidney disease models, magnetic resonance imaging, in vivo imaging system spectra, and confocal microscopy.